Metabarcoding of fecal DNA shows dietary diversification in wolves substitutes for ungulates in an island archipelago. Issue 1 (20th January 2021) - Roffler, Gretchen H.; Allen, Jennifer M.; Massey, Aimee; Levi, Taal
Abstract: Although ungulates are the main prey of wolves ( Canis lupus ) throughout their range, substantial dietary diversity may allow wolves to persist even when ungulates are declining or rare. Alexander Archipelago wolves ( Canis lupus ligoni ) inhabit distinct mainland and island biogeographic units, each with a unique assemblage of available prey. We quantified biogeographic variability in wolf diets across the archipelago using DNA metabarcoding of prey in 860 wolf scats collected during 2010–2018 in 12 study sites. We hypothesized that wolves would increase their dietary diversity and niche breadth as the proportion of ungulate species in their diets decreased, but that this could be mediated by the availability of coastal resources. Application of DNA metabarcoding achieved fine taxonomic resolution of prey remains and identified 55 diet items representing species from 42 genera and 29 families, many previously undetected in coastal wolf diets. Overall, ungulates made up the largest proportion of wolf diets but were also most variable between study sites (occurrence per item index [O/I] = 0.130–0.851). On islands, Sitka black‐tailed deer ( Odocoileus hemionus ) were the most consumed ungulate species, whereas moose ( Alces alces ) and mountain goats ( Oreamnos americanus ) contributed more to mainland wolf diets. Wolves responded to biogeographical variation in availability of their primary prey by altering their foraging patterns. Wolves increased the number and diversity of species consumed and widened their dietary niche as the proportion of ungulates in their diet declined rather than prey switch to one or few individual diet items. Across all study sites combined, beaver ( Castor canadensis ; O/I = 0.125), marine mammals (O/I = 0.113), and black bears ( Ursus americanus ; O/I = 0.067) were important alternate prey. In areas where ungulates had become scarce, sea otters ( Enhydra lutris ) were particularly important, in one case even becoming the primary diet item suggesting that the ongoing expansion of sea otter populations postreintroduction restores an important food source for these cryptic predators. Here, we show extensive variation in the diet of wolves and elucidate regional consumer–resource interactions across an archipelagic landscape.